Improving Students’ Mastery of Noun Phrases Through The 3-Dimensional Grammar Framework - Hendrik Jacob Maruanaya; Henry Latuheru; Dian Natalia Usmany (Global Education Journal, 2026)
This study aims to explore the effectiveness of implementing the 3- Dimensional Grammar Framework in improving students’ maastery of noun phrases in the context of English as a Foreign Language (EFL) learning. The research was conducted at SMAN 5 Ambon using a Classroom Action Research (CAR) approach, which consisted of two cycles. Each cycle included the stages of planning, action, observation, and reflection. The participants of this study were 36 eleventh-grade students selected purposively. Research instruments included tests (pre-test and post-test), observation, and questionnaire. In conclusion, the systematic implementation of the 3D Grammar Framework in grammar instruction successfully enhanced students’ mastery to use noun phrases effectively. This approach is recommended as an alternative strategy in grammar teaching within EFL classrooms, as it emphasizes form, meaning, and contextual use in an integrated manner.